PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), OPERATING EXPENCES TO OPERATING INCOME RATIO (BOPO) DAN NON-PERFORMING LOAN (NPL) TERHADAP PENYALURAN KREDIT (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Perio - Annisa Intan Noorani; Agus Hermani Seno; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2014)
This study aims to examine the relationships of financial ratios Capital Adequacy Ratio ( CAR ) , Loan to Deposit Ratio ( LDR ) , Operating expences To Operating Income Ratio ( BOPO ) , and Non - Performing Loan ( NPL ) credits distribution partially and simultaneously.The data used in this study are listed banking companies in Indonesia Stock Exchange for 5 consecutive years - also , ie 2008 to 2012. The criteria used is a company whose shares are actively traded on the Stock Exchange , for 5 consecutive years . This study uses multiple regression analysis , t-test for testing the ratio - the ratio of the partial finance , and test f .The results of statistical calculation with linear regression analysis can be shown by the regression equation  Y = 32.260,676  -  1.955,127 X1  + 580,887 X2  –  2.689,451 X3 + 588,208 X4. From the regression equation it is known that the CAR, LDR ,BOPO , and NPL , jointly significant effect on Loan Portfolio . The results of the calculation of the magnitude of the coefficient of determination 0.525 . It is indicating that the CAR ,LDR , BOPO , and NPL  were able to explain the purchase decision variables by 52.5 % . While the remaining 47.5 % is explained by other variables that are not observed . Based on the results of the data analysis we can conclude the effect of the CAR , LDR, BOPO , the NPL and credits distribution has a strong degree of closeness of relationship this means that the higher the CAR , LDR , BOPO , the NPL will result in the higherCredits Distribution